Estado nutricional y nivel socioeconómico de los estudiantes de la Institución Educativa Particular “Ciro Alegría” del distrito El Porvenir. noviembre- diciembre 2016 - Nolly Loyaga, Ingrid Rosy (2017)
The main objective of this study was to determine the nutritional status and socioeconomic level of the students of the "Ciro Alegría" Educational Institution of the District of El Porvenir. November-December 2016. Weight and height measurements were performed on 107 students aged 5 to 12 years for subsequent calculation of body mass index (BMI), which were used to determine nutritional status. It was found that 65% of the students of the "Ciro Alegría" Educational Institution of the District of El Porvenir, have a normal nutritional status, 25.2% are overweight, 8.4% of the children are obese and 1.8% have a According to data obtained, socioeconomic levels were classified by means of a socioeconomic survey sent to their parents, which resulted in 81% of the students being in a higher percentage in the low level (level C) and 17% in the middle level (level B), in addition 63.5% of students are in normal state and 13.10% are overweight, both percentages are within level C, with respect to level B was obtained That 11.2% of the students are obese, these results indicate that it does not influence the socioeconomic level in the nutritional status of the students